Three-Way Crossover Network by Using Bernstein Polynomial - V. Chutchavong; S. Poungpayom; O. Sangaroon; K. Janchitrapongvej (My University, 2013)
This paper presents the design of the three-way crossover network by using Bernstein polynomial.The Bernstein polynomial is applied to the Bernstein filter which has the best characteristics with more advantages.For example, it has a maximally flat magnitude, a linear-phase and a maximally flat delay with parameters of n , K and ε .For this reason, the three-way crossover network is designed by Bernstein filter.Moreover, the analog filter is converted into the digital filter by using the bilinear transformation.Both analog filter and digital filter have better performance for designing the three-way crossover network.In addition, the experimental results at the real time of the three-way crossover network can realize via FiO Board and RapidSTM32.
Keywords: Bernstein polynomial; Digital Filter Design and Implementation